Prospects for the Indian Affiliate Marketing Industry: Growth of Affiliate Programs and Channels (Indian Journal of Management and Language (IJML), 2024)
This paper discusses affiliate marketing, in which the seller or service provider is a rewarding and fulfilling agent so-called affiliate for each visitor, which through its way to attract a dealer there, who performed some action, either directly make purchases, register to subscribe to a newsletter, or simply browse the site. Affiliate marketing drives 16% of ecommerce sales in the U.S. and Canada. Amazon’s affiliate programme, Amazon Associates, has the greatest market share among affiliate networks (46.15 percent). Affiliate marketing is one of the most effective forms of digital advertising. Increasing Internet usage worldwide is propelling the affiliate marketing industry, particularly in India. Tata Strategic Management Group titled “Affiliate Marketing in India – The Next Frontier”. There are 75 highest-paying top affiliate programmes in India for 2020, organised by niche. Affiliate marketing involves three parties: the advertiser, the publisher, and the consumer. According to STATISTICA, 84 percent of U.S. Publishers and Advertisers use affiliate marketing. Adoptability and future potential of affiliate marketing in Indian enterprises is the focus of this study paper.